Prevalence of Diarrhoeal Diseases Among Children under Five Years in East African Countries from 2012–2017 - O. E. ELMI; R. (II) P. DIOSO (Universitas Gadjah Mada, 2017)
This meta-analysis analyzed the prevalence of diarrheoal diseases among children less than fiveyears in three selected Eas African countries from 2012–2017. Search engines used Google Scholar, Proquest,and PubMed. Primarily, 300 studes were selected; hence 297 were eliminated using inclusion and exclusion criteria. The PICO (population, intervention, comparison, and outcome) guide helped in the analysis of the three selected stdies. The prevalence of diarrhoea among children less than fiveyears in the three selected EastAfrican countries from 2012 to 2017, averaged to 27% range from a minimum of 11% to a maximum of 54% of the 5478 total respondents (OR 2.07). The five-yearprevalence escalated extensively at Kenya, Ethiopia, and Somalia. There is a 207% risk of further escalation.